Nano-microencapsulamento por precipitação polimérica do óleo de Nim : caracterizações e aplicações para o controle de ácaro Tetranychus urticae (ACARI: Tetranychidade) - Horn, Martha Beatriz (2019)
The present work aims the development of biopesticide based on biodegradable nanoencapsulation Neem oil for the control of the Tetranychus urticae mite. Initially oil characterization was performed using HPLC-DAD, LC-MSMS, GCMS and TGA techniques. Nanosuspensions were then prepared with poly lactic acid (PLA) or poly Ɛ-caprolactan in order to improve the thermal and photochemical protection of the active ingredient Azadiractin and to control its release. The characterization of nanosuspensions were made by DLS, MET, HPLC-DAD and pH with results indicating nanocapsule sizes between 215 and 289 nm, polydispersity index from 0.13 to 0.25 and encapsulation efficiency greater than 93%. It should be noted, better performance of PLA compared to PCL, as well as solvent evaporation by rotation and evaporation. Both the oil and the nanosuspensions evaluated showed excellent biopesticide action both in relation to mortality and reduction of mite oviposition, highlighting the NC13Ra (PLA) sample as the most effective. These results suggest the possibility of using PLA as an alternative and competitive polymer matrix to PCL for Neem encapsulation of Neem for its use as a biopesticide.